2023
DOI: 10.1038/s43705-023-00265-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine scale sampling reveals early differentiation of rhizosphere microbiome from bulk soil in young Brachypodium plant roots

Abstract: For a deeper and comprehensive understanding of the composition and function of rhizosphere microbiomes, we need to focus at the scale of individual roots in standardized growth containers. Root exudation patterns are known to vary along distinct parts of the root even in juvenile plants giving rise to spatially distinct microbial niches. To address this, we analyzed the microbial community from two spatially distinct zones of the developing primary root (tip and base) in young Brachypodium distachyon grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The quantity, composition, and distribution of rhizosphere exudates mainly depend on root morphology, plant development, and plant species (Liu et al 2022). It was found that the exudates were unevenly distributed in different root morphologies and structures, such as young lateral roots, root hairs, and old main roots (Acharya et al 2023). It is reasonable to think that the difference in microbial community diversity in different parts of the root system of Camellia sinensis L. is closely related to root exudates.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity, composition, and distribution of rhizosphere exudates mainly depend on root morphology, plant development, and plant species (Liu et al 2022). It was found that the exudates were unevenly distributed in different root morphologies and structures, such as young lateral roots, root hairs, and old main roots (Acharya et al 2023). It is reasonable to think that the difference in microbial community diversity in different parts of the root system of Camellia sinensis L. is closely related to root exudates.…”
Section: Discussionmentioning
confidence: 99%
“…The compact EcoFAB size limits the number of plant species to small plants. Notably, recent research demonstrated that the previous EcoFAB 1.0 design did not impose space constraints on Brachypodium biomass and root microbiome structure within a 14-day growth period compared to traditional pots ( 54 ). Grasses larger than B. distachyon , such as wheat, rice, maize, sorghum, or switchgrass, can be grown only during the early seedling developmental stages to avoid crowding inside the EcoFAB 2.0 device.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment inoculum consisted of tightly root-associated rhizosphere soil that came from Brachypodium distachyon grown in soil collected from Angelo Coast Range Reserve (pH 5.75 ± 0.37), California (39° 44′ 21.4′′ N 123° 37′ 51.0′′ W) and in three types of containers: fabricated ecosystems (EcoFABs), pots and test tubes ( Acharya et al, 2023 ). The loosely bound and tightly bound soil from the base and tip of the 14-day old Brachypodium distachyon roots were combined from each container type in order to prepare inocula for subsequent enrichments.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we developed a systematic and standardized framework to generate RCC that optimally represent the rhizosphere microbiome of Brachypodium distachyon and satisfies all the above criteria. Previously, we grew young Brachypodium distachyon using natural soil in standardized fabricated ecosystems (EcoFABs; Zengler et al, 2019 ) as well as conventional pots and tubes under controlled conditions, and demonstrated that the rhizosphere microbiome of Brachypodium was clearly distinct from bulk soil microbiome irrespective of the growth container ( Acharya et al, 2023 ). Subsequently, in this current study, using the naturally selected co-localized root microbiome as inoculum, we performed a large number of high-throughput enrichments to derive rhizobiome relevant RCC.…”
Section: Introductionmentioning
confidence: 99%